2020
DOI: 10.31167/csecfv3i45.19883
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del cambio global en los robledales de Quercus petraea en el NE de la Península Ibérica

Abstract: El roble albar Quercus petraea se encuentra ampliamente presente en el centro de Europa. Las poblaciones del NE de la Península Ibérica se encuentran en su límite meridional de distribución y las de condiciones más mediterráneas en el xeric limit para esta especie. Los resultados de la tesis, muestran que la comunidad ha cambiado su composición de especies des de la segunda mitad del s. XX, pero de forma sensiblemente diferente según cada región. La dinámica de los robledales de roble albar es su recuperación … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Nevertheless, during the 20 th century, subsequent changes and the abandonment of forestry practices led to the expansion of forest coverage on the NE Iberian Peninsula (Vila, 1999;Boada, 2002;Gordi, 2009;Bou Manobens et al, 2015), as was similarly reported for Montseny sessile oak forests, which have expanded and become more dense , 2019b. As a consequence of this intensive exploitation in the past, there is now a significant lack of mature forests in Catalonia (Mallarach et al, 2013), and only a few ancient and mature sessile oak forests remain (Bou, 2019;Bou & Vilar, 2019b). The same problem has been reported for sessile oak and pedunculate oak (Quercus robur) throughout Europe (Saniga et al, 2014).…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Nevertheless, during the 20 th century, subsequent changes and the abandonment of forestry practices led to the expansion of forest coverage on the NE Iberian Peninsula (Vila, 1999;Boada, 2002;Gordi, 2009;Bou Manobens et al, 2015), as was similarly reported for Montseny sessile oak forests, which have expanded and become more dense , 2019b. As a consequence of this intensive exploitation in the past, there is now a significant lack of mature forests in Catalonia (Mallarach et al, 2013), and only a few ancient and mature sessile oak forests remain (Bou, 2019;Bou & Vilar, 2019b). The same problem has been reported for sessile oak and pedunculate oak (Quercus robur) throughout Europe (Saniga et al, 2014).…”
Section: Introductionmentioning
confidence: 79%
“…The mean annual temperatures of the regions in this study range from 8 to 13°C, and annual precipitation ranges from 812 to 1035 mm (Table 1). The sessile oak forests grow on acidic lithology (Bou, 2019). In addition, human factors must also be included in these environmental conditions because, historically, many of these forests were exploited (a practice now abandoned), and they have also been included in different protected areas (Anon., 1996).…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations